2014
DOI: 10.1111/nep.12280
|View full text |Cite
|
Sign up to set email alerts
|

Nitric oxide production and blood pressure reduction during haemodialysis

Abstract: Nitric oxide production during haemodialysis was higher in IDD than in NIDD patients. IDH often occurred when systolic blood pressure was reduced to below 100 mmHg. The amount of NO produced during haemodialysis, which may be associated with predialysis systolic blood pressure, can be used to predict intradialysis blood pressure decrease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 33 publications
1
4
0
Order By: Relevance
“…for the development and progression of cardiovascular disorders in the case of DN is important not only to determine the role of CKD in the cardiovascular continuum, but also to develop new approaches to modern preventive nephrology. Today in the solution of the problem of ultrahigh frequency of coronary catastrophes, cardiac arrhythmias, cerebrovascular complications, congestive heart failure and sudden death in patients with type 2 diabetes with renal impairment in HD more and more importance is given to the study of chronic inflammation and ED[15, 16], because proinflammatory mediators and damaged endothelial cells are not only markers of DN progression with a negative impact on the prognosis, but also independent factors of increased cardiovascular risk[17,18, 19].In this study, DN in patients with CKD VD stage is combined with the activation of systemic manifestations of inflammationthe accumulation of CRP, TNF-ɑ, FG, which echoes the work of many authors[7,8,20] who observed cytokine aggression in case of DM and programmed HD. At the same time Hsu et al[5] do not find differences in the intensity of inflammatory process between groups of HD patients with and without DN, and Avci et al[4] report on inhibition of cellular inflammatory activity against OS under these conditions.…”
supporting
confidence: 73%
“…for the development and progression of cardiovascular disorders in the case of DN is important not only to determine the role of CKD in the cardiovascular continuum, but also to develop new approaches to modern preventive nephrology. Today in the solution of the problem of ultrahigh frequency of coronary catastrophes, cardiac arrhythmias, cerebrovascular complications, congestive heart failure and sudden death in patients with type 2 diabetes with renal impairment in HD more and more importance is given to the study of chronic inflammation and ED[15, 16], because proinflammatory mediators and damaged endothelial cells are not only markers of DN progression with a negative impact on the prognosis, but also independent factors of increased cardiovascular risk[17,18, 19].In this study, DN in patients with CKD VD stage is combined with the activation of systemic manifestations of inflammationthe accumulation of CRP, TNF-ɑ, FG, which echoes the work of many authors[7,8,20] who observed cytokine aggression in case of DM and programmed HD. At the same time Hsu et al[5] do not find differences in the intensity of inflammatory process between groups of HD patients with and without DN, and Avci et al[4] report on inhibition of cellular inflammatory activity against OS under these conditions.…”
supporting
confidence: 73%
“…Activating the endothelial nitric oxide synthase (eNOS) in the vascular endothelial cells will promote the synthesis and release of NO which can penetrate the cell membrane and diffuse to the adjacent smooth muscle cells. In the smooth muscle cells, NO binds to the Fe 2+ which is the hemoglobin component of the guanylate cyclase followed by elevating the cGMP levels, activating the protein kinase, phosphodiesteric acid, and ion channels, resulting in the vessel smooth muscle relaxation and vasodilatation, and increasing blood perfusion (BP) [ 12 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although NO is a small, easily diffusible molecule by the dialysis membrane, its levels significantly increase during HD [ 34 ]. High blood NO levels are associated with hyperactivation of macrophage activity by both uremia and HD procedure itself [ 32 ].…”
Section: Immunological Dysfunction In Hdmentioning
confidence: 99%
“…Derangement and dysregulation of thymus functions in ESRD patients could reflect the reduction of naive T cells [ 55 ]. Further, IDO1 activity and NO formation also contribute to T-cell immunosuppression and Treg activation [ 33 , 34 ]. The pivot of uremic toxins in promoting endothelial dysfunction and thereby vascular complications has recently re-emerged.…”
Section: Immunological Dysfunction In Hdmentioning
confidence: 99%